Algengi augn- og munnþurrks á Íslandi með hliðsjón af heilkenni Sjögrens - Jórunn Atladóttir; Ólafur Grétar Guðmundsson; Holbrook, Peter; Ragnar Sigurðsson; Björn Guðbjörnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objectives: Sjoegren' syndrome is one of the most common inflammatory systemic rheumatic disorders. The syndrome is characterised by tiredness, pain problems and mucosal dryness. The goal of this study is to elucidate the prevalence of sicca symptoms in the Icelandic population and to calculate the preliminary prevalence value for Sjoegren' syndrome in Iceland. Material and methods: Random sample was retrieved from two age groups; 40-49 and 70-75 years Icelandic inhabitants of Reykjavík and Akureyri. Questionnaire with 14 questions of the most common symptoms of Sjoegren' syndrome was mailed to those sampled. A small sample was evaluated by Schirmer-I test, tear film break up time (BUT) and Rose Bengal score for keratoconjunctivitis sicca (KCS) and unstimulated salivary flow rate was performed. Results: The questionnaire was sent to 621 subjects, 300 male and 321 female. The response rate was 74%. Of those 20.3% had subjective symptoms of dry eyes and 12.0% of dry mouth according to the six questions used in the European classification criteria (EEC). The prevalence of both was higher in females (p<0.05). Of the 23 subjects who reported sicca symptoms, fatigue and pain problems; 26% had abnormal Shirmer-I test, 13% had abnormal BUT and 39% had abnormal salivary flow rate, two of those individuals fulfilled the EEC criteria for Sjoegren' syndrome (0.2%; 0-0.5%, 95% CI). None in the age and sex matched control group fulfilled the EEC criteria. Conclusion: The subjective symptoms of dry eye and dry mouth are common in Iceland, as are the three major symptoms of Sjoegren' syndrome. Standardised objective diagnostic criteria is necessary when the diagnosis of the syndrome is made. Inngangur: Heilkenni Sjögrens er samkvæmt erlendum rannsóknum einn af algengari fjölkerfasjúkdómum. Sjúkdómurinn einkennist af dagsþreytu, stoðkerfisverkjum og þurrkeinkennum frá slímhúðum. Algengi augn- og munnþurrks er ekki þekkt hér á ...